2003
DOI: 10.4049/jimmunol.170.8.4139
|View full text |Cite
|
Sign up to set email alerts
|

Communication Between NF-κB and Sp1 Controls Histone Acetylation Within the Proximal Promoter of the Monocyte Chemoattractant Protein 1 Gene

Abstract: The induction of the monocyte chemoattractant protein 1 gene (MCP-1) by TNF occurs through an NF-κB-dependent distal regulatory region and an Sp1-dependent proximal regulatory region that are separated by 2.2 kb of sequence. To investigate how these regions coordinate activation of MCP-1 in response to TNF, experiments were performed to examine the role of coactivators, changes in local chromatin structure, and the acetylation of histones at the MCP-1 regulatory regions. An E1a-sensitive coactivator was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 40 publications
5
73
1
Order By: Relevance
“…Results from our ChIP assays further indicated that Taxmediated transcriptional activation of the hTERT promoter may also occur through an increased binding of Sp1, a transactivator of the hTERT promoter. 34 Consistent with this hypothesis, several reports have demonstrated that Tax stimulates transcription of various cellular promoters through Sp1, 35,36 that Sp1 binding sites can be positively regulated by NF-B factors, 56,57 and that c-Myc and Sp1 cooperatively function in activating the hTERT promoter. 58,59 In agreement with the study by Gabet et al, 22 when an hTERT promoter luciferase construct that covers from Ϫ255 to ϩ40 (pBT-255) 60 was used, we found Tax to have a repressive effect that was dependent on the downstream E-box (not shown).…”
Section: Discussionmentioning
confidence: 64%
“…Results from our ChIP assays further indicated that Taxmediated transcriptional activation of the hTERT promoter may also occur through an increased binding of Sp1, a transactivator of the hTERT promoter. 34 Consistent with this hypothesis, several reports have demonstrated that Tax stimulates transcription of various cellular promoters through Sp1, 35,36 that Sp1 binding sites can be positively regulated by NF-B factors, 56,57 and that c-Myc and Sp1 cooperatively function in activating the hTERT promoter. 58,59 In agreement with the study by Gabet et al, 22 when an hTERT promoter luciferase construct that covers from Ϫ255 to ϩ40 (pBT-255) 60 was used, we found Tax to have a repressive effect that was dependent on the downstream E-box (not shown).…”
Section: Discussionmentioning
confidence: 64%
“…These results, together with the FTOC experiments, suggested a preferential role for the classical NF-κB pathway in Aire gene regulation; however, we could not rule out possible involvement of the RelB/p52 complex. Similar to the Aire gene, the CCL2 gene is distal to two closely positioned NF-κB sites, and these sites interact with a proximal Sp1 site in response to TNF-α [47]. CNS1 enhancer region is critical for Aire expression and is only active in mTECs, however it is not sufficient as Aire is regulated by an Sp1 binding site and DNA hypomethylation in the proximal promoter region [32,48].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence demonstrates that chromatin modification is another important mechanism that regulates cytokine expression (Barth and Imhof 2010;Bartova et al 2008;Kouzarides 2007;Strahl and Allis 2000). Many immune related genes such as MCP-1, TNF-α, IL-12, and IL-4 are regulated by epigenetic changes characterized by histone metylation and acetylation (Weinmann et al 1999;Fields et al 2002;Barthel and Goldfeld 2003;Boekhoudt et al 2003;Goriely et al 2003;Wen et al 2008). Furthermore, TLRinduced chromatin modification of H3K4me3 and histone acetylation are shown to control the inflammation by silencing the pro-inflammatory mediators (Foster et al 2007).…”
Section: Discussionmentioning
confidence: 99%